2019
DOI: 10.5194/hess-23-2207-2019
|View full text |Cite
|
Sign up to set email alerts
|

Reactive transport with wellbore storages in a single-well push–pull test

Abstract: Abstract. Using the single-well push–pull (SWPP) test to determine the in situ biogeochemical reaction kinetics, a chase phase and a rest phase were recommended to increase the duration of reaction, besides the injection and extraction phases. In this study, we presented multi-species reactive models of the four-phase SWPP test considering the wellbore storages for both groundwater flow and solute transport and a finite aquifer hydraulic diffusivity, which were ignored in previous studies. The models of the we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The Borden site of Canada (Sudicky, 1988) is one example of weak aquifer heterogeneity. Wang et al (2018) employed a stochastic modeling technique to test the assumption of homogeneity associated with the SWPP test and found that such an assumption could be used to approximate a heterogeneous aquifer when the variance of spatial hydraulic conductivity was small.…”
Section: Model Statement Of the Swpp Testmentioning
confidence: 99%
See 4 more Smart Citations
“…The Borden site of Canada (Sudicky, 1988) is one example of weak aquifer heterogeneity. Wang et al (2018) employed a stochastic modeling technique to test the assumption of homogeneity associated with the SWPP test and found that such an assumption could be used to approximate a heterogeneous aquifer when the variance of spatial hydraulic conductivity was small.…”
Section: Model Statement Of the Swpp Testmentioning
confidence: 99%
“…Similar to other aquifer tests, the SWPP test is a forcedgradient groundwater tracer test, and analytical solutions are often preferred to determine the in situ aquifer properties, due to the computational efficiency. Currently, many analytical models are available for various scenarios of the SWPP tests (Gelhar and Collins, 1971;Huang et al, 2010;Chen et al, 2017;Schroth and Istok, 2005;Wang et al, 2018). However, these studies are based on a common underlying assumption, i.e., that the studied aquifer was isolated from adjacent aquitards.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations